PERBANDINGAN PENERAPAN MODEL CAPITAL ASSET PRICING MODEL (CAPM) DAN ARBITRAGE PRICING THEORY (APT) DALAM MEMPREDIKSI RETURN SAHAM (STUDI PADA PERUSAHAAN SEKTOR INDUSTRI BARANG KONSUMSI YANG TERDAFTAR DI BEI PERIODE 2016-2017) - Deasy Dwi Komaini; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThis study is to determination the difference in accuracy between the CAPM and APT models in predicting stock returns in the company. This type of research uses a quantitative approach using descriptive comparative methods. The data used is secondary data, obtained by documentation techniques, namely by searching and collecting annual report data and shares obtained from the website. The population that is the object of this research is the Consumer Goods Industry Sector Company listed on the Indonesia Stock Exchange in the period 2016-2017, which is as many as 42 companies. The sample selection used purposive sampling technique, so that 37 companies were obtained.The data analysis technique in this study uses the CAPM (Capital Asset Pricing Model), APT (Arbitrage Pricing Theory), and MAD (Mean Absolute Deviation) models. Measuring tool used to measure accuracy in predicting these stocks by looking for actual Returns, Return Market, Beta values (Risk), Expected Return, and comparing them with MAD (Mean Absolute Deviation)The results of data analysis show that: Based on the calculations of MADCAPM and MADAPT, that the CAPM method is better and more accurate than the APT model in predicting the return of shares of the Industrial Consumer Goods Industry Sector.Keywords : CAPM,APT, Return Actual, Expected Return, Saham, MAD